2022
DOI: 10.3390/pharmaceutics14020258
|View full text |Cite
|
Sign up to set email alerts
|

Combined Therapeutics for Atherosclerosis Treatment Using Polymeric Nanovectors

Abstract: Atherosclerosis is an underlying risk factor in cardiovascular diseases (CVDs). The combination of drugs with microRNAs (miRNA) inside a single nanocarrier has emerged as a promising anti-atherosclerosis strategy to achieve the exploitation of their complementary mechanisms of action to achieve synergistic therapeutic effects while avoiding some of the drawbacks associated with current systemic statin therapies. We report the development of nanometer-sized polymeric PLGA nanoparticles (NPs) capable of simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Statin treatment represents a milestone, but the effects of systemic administration could be enhanced by targeted delivery of statins, through polymers and nanoparticles [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statin treatment represents a milestone, but the effects of systemic administration could be enhanced by targeted delivery of statins, through polymers and nanoparticles [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies showed encouraging results in inflammation reduction when using statins as targeted therapy. According to Leal et al [ 76 ], PLGA can be used as a carrier in delivering atorvastatin combined with miRNA-124a, drastically reducing the levels of proinflammatory cytokines such as TNF-α and IL-6, and of reactive oxygen species (ROS), in LPS-activated macrophages and vessel endothelial cells.…”
Section: Biological and Clinical Effectsmentioning
confidence: 99%
“…Considering the growing interest in nanomedicine, numerous efficient nano-preparations have been utilized in the treatment of atherosclerosis. It is conceivable to combine genes that promote atherosclerosis plaque regression with nano-carriers through entrapment, encapsulation, adsorption, or covalent bonding to create a "nano-drug delivery system" for achieving effective early treatment of atherosclerosis [ 99 ].…”
Section: Opportunities For Precision Medicinementioning
confidence: 99%
“…They can be synthetically or chemically modified to improve gene transfection efficiency and reduce cytotoxicity [ 104 ]. Compared with neutral polymers, cationic polymers have better targeting capability [ 105 , 106 ]. Moreover, cationic polymers are positively charged, caused by the amine group in their structures.…”
Section: Sirna Nanocarriersmentioning
confidence: 99%